A Buddhist manual of psychological ethics (Buddhist psychology) of the fourth century BC: being a translation, now made for the first time, from the original Pāli of the first book in the Abhidhamma-piṭaka, entitled Dhamma-sangaṇi (compendium of states or phenomena) - Davids, Caroline Rhys (Munshiram Manoharlal Publishers Pvt. Ltd, 2016)
Tipiṭaka / Abhidhammapiṭaka / Dhammasaṅgaṇī